Cost-Effectiveness of Computed Tomography Angiography in Management of Tiny Unruptured Intracranial Aneurysms in the United States. Issue 9 (September 2019) - Wu, Xiao; Matouk, Charles C.; Mangla, Rajiv; Forman, Howard P.; Gandhi, Dheeraj; Sanelli, Pina; Malhotra, Ajay
Abstract : Background and Purpose—: Our study aims to evaluate the cost-effectiveness of computed tomography angiography (CTA) for surveillance of tiny unruptured intracranial aneurysms and the impact of CTA radiation-induced brain tumor on the overall effectiveness of CTA. Methods—: A Markov decision model was constructed from a societal perspective starting with patients 30-, 40-, or 50-year-old, with incidental detection of unruptured intracranial aneurysm ⩽3 mm and no prior history of subarachnoid hemorrhage. Five different management strategies were assessed (1) annual CTA surveillance, (2) biennial CTA, (3) CTA follow-up every 5 years, (4) coiling and subsequent magnetic resonance imaging follow-up, and (5) annual CTA surveillance for the first 2 years, followed by every 5-year CTA follow-up. Probabilistic, 1-way, and 2-way sensitivity analyses were performed. Results—: The base case calculation shows every 5-year CTA follow-up to be the most cost-effective strategy, and the conclusion remains robust in probabilistic sensitivity analysis. It remains the dominant strategy when the annual rupture risk of nongrowing unruptured intracranial aneurysms is smaller than 2.66% or the rupture risk in growing aneurysms is <57.4%. The radiation-induced brain cancer risk is relatively low, and sensitivity analysis shows that the radiation-induced cancer risk does not influence the conclusions unless the risk exceeds 663-fold of the base case values. Conclusions—: Given the current literature, every 5-year CTA imaging follow-up is the cost-effective strategy in patients with aneurysms ⩽3 mm, resulting in better health outcomes and lower healthcare spending. Patients with aneurysms at high risk of rupture might need more aggressive management. Abstract : Supplemental Digital Content is available in the text.